Cross-laminated timber–concrete composite structural floor system: A state-of-the-art review. (December 2021) - Siddika, Ayesha; Mamun, Md. Abdullah Al; Aslani, Farhad; Zhuge, Yan; Alyousef, Rayed; Hajimohammadi, Ailar
Highlights: Critical overview on the Cross-laminated timber (CLT)-concrete floor system. CLT-concrete possesses high out-of-plane load bearing capacity. CLT–concrete composite can be effectively developed with 3–5 times higher strength capacity than ordinary timber or concrete system. Durability, acoustic and thermal performance of CLT-concrete system are satisfactory. Abstract: Composite construction elements are gaining extensive attention due to their high performance and reliability. Timber–concrete composite is one of the well-known engineered products of global interest. The cross-laminated timber (CLT) is a plate-like quasi-rigid composite that is usually composed of an uneven number of layers of solid timber board. The timber boards are generally placed side-by-side and arranged crosswise in CLT. The anisotropy in single timber boards is reliably adjusted, and its out-of-plane load bearing capacity is improved. The CLT members show low bending strength and resistance to global stability. The CLT–concrete composite has developed and showed approximately 3–5 times higher strength capacity than the conventional timber or concrete structures. This study aims to review the current practice and available guidelines for the CLT–concrete floor system. The basic required information on the design and construction and performance of the aforementioned system is described based on the current practices. This review can guide prospective researchers and users regarding the application of the CLT–concrete composite. The CLT–concrete elements need to be designed and constructed following the current code of practice and studies guidelines to achieve optimal performance. The design, construction, and performance of the CLT-concrete system are dependent on timber properties, connection systems, and slab details. This composite floor system possesses good performance under various loading conditions if adequately designed and constructed.